Facebook Group Use among Parents of Children with Tracheostomy. (March 2020) - Huestis, Mikayla J.; Kahn, Chase I.; Tracy, Lauren F.; Levi, Jessica R.
Tracheotomy in the pediatric population creates unique challenges for parents. Parents often feel underprepared to provide adequate tracheostomy care. Social media is used as a resource for many medical conditions. We looked at Facebook use among parents of children with a tracheostomy to determine how this resource is used as support and to assess common concerns that require improved education prior to discharge. We joined 8 Facebook groups focused on children with a tracheostomy, analyzed the posts for how the groups were used, and identified recurring content. The primary focus of the groups was parental support and general information about tracheostomy care. A common theme identified was patients not receiving medical supplies on time, and groups provided a forum to obtain supplies. Groups also provided general advice about how to travel with a tracheostomy and medical advice, such as when to worry about blood in the tracheostomy tube.